2009
DOI: 10.1248/bpb.32.1765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Insulin Uptake in Rat Alveolar Type II and Type I-Like Epithelial Cells

Abstract: The alveolar epithelium is comprised of type II and type I cells, which are two morphologically and functionally different epithelial cells. Alveolar type I cells, which are squamous and cover more than 90% of the alveolar surface area, play a major role in gas exchange. 1,2) On the other hand, alveolar type II cells are cuboidal and outnumber type I cells, although type II cells occupy less than 10% of the surface area even when their apical microvilli are taken into consideration.1,2) In addition, type II ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
5
9
0
Order By: Relevance
“…In the RLE-6TN alveolar type II epithelial cell line, albumin transported by a non-caveolae transport mechanism, predominantly a clathrin-dependent process, was tracked to lysosomes and the rate of degradation measured (Yumoto et al 2006). In the latter study the apparent uptake of fluorescently labelled albumin was approximately 1,100 ng/mg cell protein/60 min, in general agreement with their other measurements in primary type II and type I rat alveolar epithelial cells of between 800 and 6,000 ng/mg cell protein/60 min; the latter is equivalent to 0.2–0.7 pg/cell/60 min (calculated from: Ikehata et al 2008; Ikehata et al 2009). Moreover, fluorimetric analysis after SDS–PAGE indicated that during this continuous uptake process approximately 16% of the albumin was degraded after 60 min.…”
Section: Uptake Of Albumin Into the Cell And Its Fatesupporting
confidence: 89%
“…In the RLE-6TN alveolar type II epithelial cell line, albumin transported by a non-caveolae transport mechanism, predominantly a clathrin-dependent process, was tracked to lysosomes and the rate of degradation measured (Yumoto et al 2006). In the latter study the apparent uptake of fluorescently labelled albumin was approximately 1,100 ng/mg cell protein/60 min, in general agreement with their other measurements in primary type II and type I rat alveolar epithelial cells of between 800 and 6,000 ng/mg cell protein/60 min; the latter is equivalent to 0.2–0.7 pg/cell/60 min (calculated from: Ikehata et al 2008; Ikehata et al 2009). Moreover, fluorimetric analysis after SDS–PAGE indicated that during this continuous uptake process approximately 16% of the albumin was degraded after 60 min.…”
Section: Uptake Of Albumin Into the Cell And Its Fatesupporting
confidence: 89%
“…These results indicate that energy-dependent, saturable mechanism, most likely receptor-mediated endocytosis, is involved in FITC-insulin uptake by RLE-6TN cells. These characteristics are essentially the same as those observed for primary cultured alveolar type II epithelial cells (Ikehata et al, 2009), though the apparent affinity seems to be somewhat lower in RLE-6TN cells.…”
Section: Discussionsupporting
confidence: 79%
“…Uptake experiments were performed as described previously (Ikehata et al, 2009;Tagawa et al, 2008;Takano et al, 2002). Briefly, RLE-6TN cells grown on 35-mm culture dishes were used.…”
Section: Uptake Of Fitc-insulin By Rle-6tn Cellsmentioning
confidence: 99%
See 2 more Smart Citations